Well-dispersive Pt nanoparticles grown on 3D nitrogen- and sulfur-codoped graphene nanoribbon architectures: highly active electrocatalysts for methanol oxidation. (September 2021) - Huang, H.; Guo, X.; Yan, M.; Meng, W.; Xue, Y.; Xiao, D.; Jiang, Q.; Yang, L.; He, H.
Abstract: Although platinum and its derivatives are generally recognized as the most efficient anode materials for direct methanol fuel cells, their high usage costs and poor poison tolerance largely hamper the large-scale commercial application. Here, we present a convenient bottom-up approach to the fabrication of well-dispersive Pt nanoparticles grown on 3D nitrogen- and sulfur-codoped graphene nanoribbon (Pt/NS-GNR) architectures via a self-assembly process. With a series of intriguing structural features, including large specific surface area, 3D interpenetrating porous carbon networks, a large presence of N and S dopants and homogeneous dispersion of ultrafine Pt nanoparticles, the obtained Pt/NS-GNR hybrid possesses a large electrochemically active surface area, high electrocatalytic activity, reliable long-term durability, as well as good antitoxic ability toward methanol oxidation reaction, far surpassing those of conventional Pt catalysts deposited on commercial carbon black, carbon nanotubes, graphene, and undoped graphene nanoribbon supports. Theoretical simulations further reveal that there are strong electronic interactions between metal and matrix, which could not only immobilize the Pt particles onto the 3D NS-GNR frameworks but also weaken the CO adsorption on the catalytic sites, thereby synergistically promoting the methanol oxidation catalytic efficiency. Graphical abstract: A convenient bottom-up approach is developed to fabricate well-dispersive Pt nanoparticles grown on 3D N- and S-codoped graphene nanoribbon architectures. Owing to the 3D cross-linked porous networks, optimized electronic structure, homogeneous Pt dispersion, and good electron conductivity, the resulting hybrid catalyst possesses superior electrocatalytic properties toward methanol oxidation. Image 1 Highlights: 3D N and S codoped graphene nanoribbon is constructed by a bottom-up approach. The uniform dispersion of ultrafine Pt on graphene nanoribbon surface is achieved. The cross-linked networks facilitate the transportation of both electrons and ions. The resulting catalyst exhibits superior methanol oxidation performance.